Harnessing the Power of Demographic Forecasts: A Key to Shaping Economic Development Strategy (Journal of Universal Science Research, 2023)
This article discusses the growing significance of demographic forecasts in shaping effective economic development strategies. It highlights the benefits of using accurate population projections to tailor social services, workforce development, and urban planning. The article emphasizes the role of demographic forecasts in addressing economic inequalities and anticipating the impact of aging populations. By utilizing this data-driven approach, governments and businesses can make informed decisions to foster sustainable growth and prosperity.